Seasonal variation of right heart function in elite skiers-racers: an echocardiographic study - Dernovoj, B.; Nuzhny, V.; Prosheva, V. (European Journal of Applied Physiology, 2022)
Purpose To examine seasonal variation of the right heart (RH) structure and function in elite skiers-racers.